Baggie Art Enterprise / Nurfarisha Suraya Hasmadi - Hasmadi, Nurfarisha Suraya (2020)
Baggie Art Enterprise is a new custom-made tote bag line in Kedah that manufactures tote bag and more importantly made with 100% hands on art. We target to males and females between the ages of 13 and above who enjoys art as their fashion. We can help customers develop a design for their tote bag either in the formof painting, drawing or sketching but not printing. Baggie Art shop will open everyday except for Friday and our online websites and social media services are available opened for 24 hours to taking orders by the customer. Our headquarters located at LOT 180, Jalan Perdana Heights 2/2, Bandar Amanjaya, 08000 Sungai Petani, Kedah. This location also considers local transport links, particularly main roads and motorways and the absolute our business location can be found using GPS.